Why we should be concerned about accountable care organisations in England's NHS. (30th January 2018) - Pollock, Allyson M; Roderick, Peter
Abstract : The government and NHS England's plans for a major reorganisation of the health and adult social care system must come under greater scrutiny, argue Allyson Pollock and Peter Roderick